"We're getting somewhere": Development and implementation of a framework for the analysis of productive science discourse. Issue 1 (13th November 2018) - Grimes, Paul; McDonald, Scott; van Kampen, Paul
Abstract: Sense‐making and argumentation are two common ways to frame student discourse. The former emphasizes the process of students coming to an understanding, the latter the logical and rhetorical structure of the product. When we investigated the discourse of two groups of preservice science teachers in an environment that fosters productive disciplinary engagement, we found that elements of both sense‐making and argumentation pervaded the discourse as the preservice teachers engaged in the scientific practice of developing an explanation of a complex phenomenon. We have developed a framework based on, but extending that of Toulmin that allowed us to capture the to‐and‐fro nature of the development of an explanation by using elements of argumentation and sense‐making as well as transactivity. Using the framework we were able to characterize almost all utterances of the 40‐min discourse of both groups. Both groups arrived at a similar point of conceptual convergence, even though the interactions that took place during the activity were of quite a different nature. We detail the affordances of our framework and contrast them with those of purely argumentation‐based frameworks.